2018
DOI: 10.3390/ma12010103
|View full text |Cite
|
Sign up to set email alerts
|

Light Concentration by Metal-Dielectric Micro-Resonators for SERS Sensing

Abstract: Metal-dielectric micro/nano-composites have surface plasmon resonances in visible and near-infrared domains. Excitation of coupled metal-dielectric resonances is also important. These different resonances can allow enhancement of the electromagnetic field at a subwavelength scale. Hybrid plasmonic structures act as optical antennae by concentrating large electromagnetic energy in micro- and nano-scales. Plasmonic structures are proposed for various applications such as optical filters, investigation of quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 238 publications
(342 reference statements)
0
22
0
1
Order By: Relevance
“…Furthermore, this group also showed that the thickness of the metallic layer (for gold) has an effect on the SERS enhancement [59]. Lastly, other groups also demonstrated SERS enhancements with other shapes of Si nanosystems such as a tip-shaped silicon metasurface coated with gold nanoparticles [67,68], a hybrid Si nanospheroid network ornamented with gold nanospheres [69], silver-coated Si nanopores [70], or Si nanowire arrays coated silver nanoparticles [71,72]. To conclude Section 2, the interests of the metal-coated Si nanosystems are the use of fabrication techniques known as large-surface techniques, and also the plasmonic coupling between the metallic layer/nanoparticles and the semiconducting silicon substrate [38,58,73] in order to potentially improve the Raman enhancement.…”
Section: Sers Performances Of Metal-coated Si Nanosystems For Chemicamentioning
confidence: 86%
“…Furthermore, this group also showed that the thickness of the metallic layer (for gold) has an effect on the SERS enhancement [59]. Lastly, other groups also demonstrated SERS enhancements with other shapes of Si nanosystems such as a tip-shaped silicon metasurface coated with gold nanoparticles [67,68], a hybrid Si nanospheroid network ornamented with gold nanospheres [69], silver-coated Si nanopores [70], or Si nanowire arrays coated silver nanoparticles [71,72]. To conclude Section 2, the interests of the metal-coated Si nanosystems are the use of fabrication techniques known as large-surface techniques, and also the plasmonic coupling between the metallic layer/nanoparticles and the semiconducting silicon substrate [38,58,73] in order to potentially improve the Raman enhancement.…”
Section: Sers Performances Of Metal-coated Si Nanosystems For Chemicamentioning
confidence: 86%
“…In the second and last part, the discussed topics are devoted to chemistry and sensing, such as surface-enhanced fluorescence, surface-enhanced Raman scattering (SERS), sum-frequency generation (SFG) spectroscopy, and electrocatalysis by using plasmonics [34,35,36,37,38,39,40]. Concerning the surface-enhanced fluorescence, Lu et al numerically demonstrated a high enhancement effect of the fluorescence signal obtained with a hybrid metal-dielectric nano-aperture antenna consisting of silicon and gold layers [34].…”
Section: Synopsismentioning
confidence: 99%
“…Another approach for obtaining an excellent SERS activity is to use luminescent-plasmonic material based on neodymium(III)-doped yttrium–aluminium–silicate microspheres with gold nanoparticles [ 45 ]. In addition, hybrid metal/Si nanostructures allowed achieving substantial values of EF (10 7 –10 10 ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. These hybrid nanostructures based on silicon (semiconductor) have the property of biocompatibility, and a low cost of production.…”
Section: Introductionmentioning
confidence: 99%